Standardization of agro-techniques for aeroponic potato (Solanum tuberosum) minitubers under generation-0 - SADAWARTI, MURLIDHAR J; SAMADHIYA, R K; SINGH, R K; SINGH, S P; BUCKSETH, TANUJA; RAWAL, SANJAY; SINGH, VINAY; KATARE, SUBHAS; ROY, SATYAJIT; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2020)
Since, very less information is available regarding the agro-techniques of hi-tech seed potato minitubers production, therefore an experiment was conducted to evaluate planting geometry and different doses of nitrogen for multiplication of aeroponic minitubers of potato (Solanum tuberosum L.) under net house conditions of north-central plains of India. 30 cm × 15 cm (97.44) plant geometry and 150 kg N/ha (95.81) and 180 kg N/ha (96.98) N dose recorded significantly higher emergence %. Linear increase in plant height was recorded with 120, 150 and 180 kg N/ha dose over 75 kg N/ ha (44.1 cm). Planting geometry 45 cm × 10 cm (34.71) and N dose 150 kg N (35.71) recorded significantly lowest per cent of